2013
DOI: 10.1038/cdd.2013.179
|View full text |Cite
|
Sign up to set email alerts
|

Selective CDK9 inhibition overcomes TRAIL resistance by concomitant suppression of cFlip and Mcl-1

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) can induce apoptosis in many cancer cells without causing toxicity in vivo. However, to date, TRAIL-receptor agonists have only shown limited therapeutic benefit in clinical trials. This can, most likely, be attributed to the fact that 50% of all cancer cell lines and most primary human cancers are TRAIL resistant. Consequently, future TRAIL-based therapies will require the addition of sensitizing agents that remove crucial blocks in the TRAIL apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 56 publications
10
110
0
Order By: Relevance
“…The mRNA expression profiling data showed an increase in the transcript levels of the antiapoptotic gene MCL1 in the HT29 cell line. Previously, we had seen this with seliciclib treatment but the expression of MCL1 protein was rapidly decreased in response to CDK inhibition (Whittaker et al ., ) as has been described for several other CDK9 inhibitors (Gregory et al ., ; Lemke et al ., ; Ma et al ., ). Further RT‐qPCR analysis showed that MCL1 mRNA was initially inhibited in all three cancer cell lines at 4 h but was substantially increased in HT29 and RKO cells by both seliciclib and CCT068127 at 24–48 h. However, MCL1 protein levels were decreased by both compounds at 4–48 h in HT29 and COLO205 cells, whereas RKO cells showed a decrease at 4 h and recovery at 24–48 h. Given the effect of CDK2 and CDK9 inhibition on the cell cycle and global transcriptional regulation, presumably sustained MCL1 protein suppression at 24–48 h is due to either inhibition of translation of the mRNA or accelerated protein degradation (Choudhary et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…The mRNA expression profiling data showed an increase in the transcript levels of the antiapoptotic gene MCL1 in the HT29 cell line. Previously, we had seen this with seliciclib treatment but the expression of MCL1 protein was rapidly decreased in response to CDK inhibition (Whittaker et al ., ) as has been described for several other CDK9 inhibitors (Gregory et al ., ; Lemke et al ., ; Ma et al ., ). Further RT‐qPCR analysis showed that MCL1 mRNA was initially inhibited in all three cancer cell lines at 4 h but was substantially increased in HT29 and RKO cells by both seliciclib and CCT068127 at 24–48 h. However, MCL1 protein levels were decreased by both compounds at 4–48 h in HT29 and COLO205 cells, whereas RKO cells showed a decrease at 4 h and recovery at 24–48 h. Given the effect of CDK2 and CDK9 inhibition on the cell cycle and global transcriptional regulation, presumably sustained MCL1 protein suppression at 24–48 h is due to either inhibition of translation of the mRNA or accelerated protein degradation (Choudhary et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…This idea is supported by the finding that CDK9 inhibition is well tolerated in animal models and patients. 16,17,31,32 However, so far, the comparison of CDK9 expression in healthy and malignant tissue was not provided. Initially, the role of CDKs was solely connected to controlling the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently this remains uninvestigated and no evidence exists as such. On the other hand, CDK9 has been identified to facilitate resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), a condition observed in 50% of all cancer cell lines (Lemke et al 2014). CDK9 inhibition may circumvent TRAIL resistance and boost cancer cell apoptosis.…”
Section: :12mentioning
confidence: 99%
“…As a consequence, targeting CDK9 may provide a unique opportunity to induce apoptosis of PCa cells by stopping their oncogenic driver, AR. Inhibiting CDK9 is known to cause minimal toxicity to normal cells (Lemke et al 2014, Li et al 2015. In vivo mouse xenograft models and phase I clinical trials have also shown that CDK9 inhibition results in minimal toxicity while maintaining effective antitumor activity (Abdullah et al 2011, Feldmann et al 2011, Nemunaitis et al 2013.…”
Section: :12mentioning
confidence: 99%